An integrated experiment for identification of best decision styles and teamworks with respect to HSE and ergonomics program: The case of a large oil refinery. (December 2015) - Azadeh, A.; Mokhtari, Z.; Sharahi, Z. Jiryaei; Zarrin, M.
Highlights: Operators of an oil refinery are assessed with respect to HSE and ergonomic factors. The efficient operators are determined based on HSE factors and their decision style. Teamwork efficiency is assessed based on different decision style combinations. DEA model is used for evaluation and optimization of the operators' efficiencies. Using the best operators in critical posts improves system's performance. Abstract: Decision making failure is a predominant human error in emergency situations. To demonstrate the subject model, operators of an oil refinery were asked to answer a health, safety and environment HSE-decision styles (DS) questionnaire. In order to achieve this purpose, qualitative indicators in HSE and ergonomics domain have been collected. Decision styles, related to the questions, have been selected based on Driver taxonomy of human decision making approach. Teamwork efficiency has been assessed based on different decision style combinations. The efficiency has been ranked based on HSE performance. Results revealed that efficient decision styles resulted from data envelopment analysis (DEA) optimization model is consistent with the plant's dominant styles. Therefore, improvement in system performance could be achieved using the best operator for critical posts or in team arrangements. This is the first study that identifies the best decision styles with respect to HSE and ergonomics factors.